Specific and Nonspecific Interactions between Methanol and Ethanol and Active Carbons - López-Ramón, María Victoria; Stoeckli, Fritz; Moreno-Castilla, Carlos; Carrasco-Marín, Francisco (My University, 2000)
The interaction of methanol and ethanol with active carbons of different origins and containing between 0.81 and 7 mmol g-1 surface oxygen has been examined by immersion calorimetry and by vapor adsorption at 293 K, benzene being the reference. The results obtained by these independent techniques are in excellent agreement. With respect to pure carbons, the surface oxygen leads to excess enthalpies of immersion of 5.32 and 2.64 J mmol-1 oxygen for methanol and ethanol. Alternatively, it appears that the affinity coefficients β(CH3OH) and β(C2H5OH), which appear in the Dubinin−Astakhov equation, are functions of the oxygen content and of the enthalpy of immersion into benzene. The limiting values, as the oxygen content tends to zero, are respectively 0.40 and 0.62, in agreement with the values quoted in the literature. It is also found that the adsorption of CO2 is not affected by the oxygen content of the surface and β(CO2) = 0.40.